Parametricism, Heuristics and Co-Creation in the Arts of Design - Uribe Mendoza, Bernardo (ACTIO Journal of technology in design, film arts and visual communication, 2021)
In 2008, architect Patrick Schuhmacher, from Zaha Hadid Architects, proposed an architectural manifesto for the 21st century, extendable to other arts of design and even to other areas of technological and artistic activity in which the human factor is associated with creation: Parametricism. In the subsequent debate, problems such as those of a new style as produce of digital technologies, and the totalizing claims of a design theory based on Niklas Luhmann’s postulates on his General Systems theory, have been repeatedly discussed. In this article, the topics of the Parametricism manifesto associated with the human factor and creation in design in the current technological environments, have been extrapolated to its plausible revision from the heuristics discipline perspective and to a possible re-definition of the co-creation concept in the arts developed by the Informal Art Movement of the mid-XX Century.